Evaluation Model and Enhancement Strategies for Teaching Reform Capacity of Art Courses in Higher Vocational Colleges - Miao, Lin (International journal of emerging technologies in learning, 2020)
In higher vocational colleges, the teaching reform of art courses faces complex problems, namely, the evaluation system is imperfect, and the evaluation model involves complex calculations. To solve these problems, this paper strives to enhance the teaching reform capacity of art courses in higher vocational colleges. Firstly, the factors affecting the said teaching reform were identified. Next, an index system was established to evaluate the teaching reform capacity. The index system was integrated with the gray theory into an evaluation model of the teaching reform capacity. Based on the evaluation results, several strategies were put forward to enhance the teaching reform capacity. The research results provide a good reference for higher vocational colleges to reform the teaching of art courses.